The Role of Family and Peer Support in Promoting Students’ School-Related Well-Being during Crisis: A Mediation Model of Basic Psychological Needs - Kamaliya, Naila; Cahyadi, Surya; Setyowobowo, Hari (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
The enforcement of physical distancing measures to mitigate the transmission of COVID-19 led the Indonesian government to implement remote learning. This situation created challenges for students’ academic well-being due to changes in their social environments. Grounded in Basic Psychological Needs Theory (BPNT; Deci & Ryan, 2000, 2017), the present study examined a model linking social support (from family, friends, and significant others) to school-related subjective well-being through the satisfaction of basic psychological needs (autonomy, relatedness, and competence) during the COVID-19 pandemic. A cross-sectional survey was conducted with 665 Indonesian students who participated in home-based learning. Data were analyzed using structural equation modeling to test the proposed hypotheses. The single-level model analysis indicated that social support was strongly associated with school-related subjective well-being, and this relationship was mediated by basic psychological needs. Further multiple-mediator analyses revealed that satisfaction of autonomy, competence, and relatedness needs mediated the relationship between family and friend support and school-related subjective well-being. However, basic psychological needs did not mediate the effect of significant others’ support on subjective well-being. These findings contribute to the literature on psychological well-being by highlighting the mediating role of basic psychological needs in the relationship between different sources of social support and students’ school-related subjective well-being.